Laboratory predictors of clinical outcomes in patients with atrial fibrillation - A. A. Sokolova; I. V. Goncharova; A. A. Vedernikov; N. S. Morozova; D. A. Napalkov (Рациональная фармакотерапия в кардиологии, 2021)
Atrial fibrillation (AF) is the most common cardiac arrhythmia in clinical practice that affects intracardiac hemodynamics and is accompanied by increased mortality due to the risk of stroke and systemic thromboembolism. In recent years, numerous studies, evaluating the use of biomarkers in AF patients, have been conducted to expand the possibility of stratification the complications risks.The aim of the review is to evaluate the possible isolated and combined predictive significance of NT-proBNP, troponin T (TnT) and D-dimer levels in the development and progression of AF and its thromboembolic complications according to published data. Determining the level of NT-proBNP can be used to diagnose cardioembolic stroke in latent forms of AF. Patients with a cardioembolic stroke have been shown to have higher BNP/NT-proBNP levels than patients with an atherothrombotic stroke and venous thromboembolism. Elevated TnT level is independently associated with AF detection as a cause of stroke. The assessment on the CHADS2 scale significantly correlates with the level of troponin I (TnI). However, it is equally important to take into account TnI level even with a low score of CHADS2. Patients with the level of TnI ≥ 0.040 pg/L are considered to be prescribed anticoagulants in the same way as the patients with high CHADS2 score. Similar results were obtained analyzing high-sensitivity cardiac troponin T (hs-cTnT) data. The level of D-dimer 0.315 mg/L was determined to be the optimal limit level for predicting the adverse functional outcome of stroke owing to AF. Patients with a high level of D-dimer have shown a high risk of developing thromboembolic and cardiovascular complications despite their taking anticoagulant drugs. D-dimer levels positively correlate with the CHA2DS2 and CHA2DS2-VASC scales of stroke risk stratification. The analysis of the biomarkers combination has revealed the increase of hs-cTnT and BNP associated with stroke in AF patients (p<0.05). However, ABC scale, including hs-cTnT and NT- pro BNP, hasn't given more accurate result in stroke predicting than CHA2DS2-VASc scale. The integration of biomarkers in predicting the risk of AF occurrence, progression and appearance of thromboembolic complications is a promising direction. An isolated level of biomarkers (hs-cTnT, NT-proBNP, D-dimer) and their combination with clinical risk factors can improve the quality of cardioembolic strokes prognosis.